Application of 4.9 GHz Timeslot Flipping Technology Based on Triple-frequency Networking in Xiwan Coal Mine - MA Xiaolong; LEI Jian; WANG Xiaoqi (Kongzhi Yu Xinxi Jishu)
Unmanned driving & remote driving transportation business in Xiwan Coal Mine requires three-dimensional coverage of wireless network with large bandwidth and low latency in light-load test area, heavy-load test area and whole mining area. In view of the difficulties of site landing, high frequency of site relocation and complex wireless environment in coal mining area, this paper puts forward a scheme of "700 MHz+2.6 GHz+4.9 GHz" triple frequency networking, which effectively solves the problem of safe, stable and efficient 5G network coverage in the whole mining area, and meets the bandwidth and delay business needs of unmanned driving&remote driving. At the same time, in order to further enhance the bandwidth of coal mining area (coal roof, stone roof), a 4.9 GHz time slot flip 1D3U scheme is proposed, which changes three downward time slots to uphill time slots, making the proportion of downward timeslot to uphill time slot from 5:3 to 1:3. After the implementation of the triple-frequency networking scheme, the proportion 50 Mbit/s upstream edge rate in the whole coal mine business area is more than 99%, and the average time delay is less than 20 ms. After the implementation of the 4.9 GHz timeslot flip 1D3U scheme, the peak rate of ascending in the core mine area increased from 290 Mbit/s to around 600 Mbit/s, which expanded the upstream bandwidth.